Controlador fuzzy takagi-sugeno aplicado a um manipulador com juntas flexíveis - Takano, Karina Assolari (2016)
This work studies the control of robotic manipulators with flexibility, specifically, the control of a planar serial manipulator with two degrees of freedom and flexibility in the joints. The main objective of this study is to design a regulation control using Parallel Distributed Compensation and Takagi-Sugeno fuzzy model, to approximate the nonlinearities of the system. The objective of the regulation control law is to provide damping to the manipulator to attenuate the vibrations in a specific configuration. The dynamic model of the manipulator studied is obtained using Lagrange-Euler principles. The regulation control performance is valued by computer simulations that prove the effectiveness of the proposed controller.